Alat Perebus Dan Pengupas Telur Ayam - Khamdi, Nur; Pratama, Tomy (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2023)
Chicken eggs are not strange among the people of Indonesia. Chicken eggs are usually consumed in the form of cooking. Processing of chicken egg that is by way of boiling and followed by stripping eggshell with purpose to make it easier to in direct consumption. With the development of technology, this work can be done by machinery, so the work becomes more effective, fast and productive. From this it will be designed tool that can boil and peel chicken eggs. Tools of boiling and peeling eggs using microcontroller ATMega8535 as a controller system, making it easier to process eggs. The working mechanism of the boiler and peeler is using DC motors, heater, and push button and ATMega8535 serves as the timer timer needed to boil the egg. Heater serves to heat the water in the pan to boil the eggs, timer from the microcontroller will be active to set the time of boiling eggs that have previously been set. When the timer has finished counting, the DC motor will be active and rotate the boiling pot until the egg is peeled and from the menu on the boilers and this chicken egg peelers have cooked eggs and middle eggs cooked on the boiled chicken egg yolk